2012
DOI: 10.4254/wjh.v4.i12.327
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease and the renin-angiotensin system: Implications for treatment

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the commonest liver disease in Western countries. Treatment of NAFLD is currently based on lifestyle measures and no effective pharmacologic treatment is available so far. Emerging evidence, mainly from animal studies, suggests that the renin-angiotensin-aldosterone system may be of major importance in the pathogenesis of NAFLD and indicates that angiotensin-converting enzyme inhibitors (ACE-I) and angiotensin receptor blockers (ARBs) as a potentially useful therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 33 publications
0
66
0
1
Order By: Relevance
“…In clinical practice, however, the usefulness of treating liver fibrosis with ARBs remains contradictory (Schneider et al, 1999;Gonzalez-Abraldes et al, 2001;Lee, 2014). A handful of randomized controlled trials suggest that ARB treatment is a potentially useful therapeutic approach in patients with nonalcoholic fatty liver disease (Paschos and Tziomalos, 2012). The nonalcoholic fatty liver disease patients benefited from telmisartan and olmesartan treatment (Enjoji et al, 2008;Colmenero et al, 2009).…”
Section: G Pathophysiological Aspects Of Angii Type 1 Receptor Activmentioning
confidence: 99%
“…In clinical practice, however, the usefulness of treating liver fibrosis with ARBs remains contradictory (Schneider et al, 1999;Gonzalez-Abraldes et al, 2001;Lee, 2014). A handful of randomized controlled trials suggest that ARB treatment is a potentially useful therapeutic approach in patients with nonalcoholic fatty liver disease (Paschos and Tziomalos, 2012). The nonalcoholic fatty liver disease patients benefited from telmisartan and olmesartan treatment (Enjoji et al, 2008;Colmenero et al, 2009).…”
Section: G Pathophysiological Aspects Of Angii Type 1 Receptor Activmentioning
confidence: 99%
“…Moreover, observational studies suggest that patients with NAFLD have increased cardiovascular risk and that CVD is the leading cause of death in this population [10][11][12][13] . Since NAFLD and CVD have many common risk factors (e.g., abdominal obesity, type 2 diabetes mellitus (T2DM), insulin resistance, inflammation and oxidative stress), the increased CVD risk in patients with NAFLD might be partly explained by their shared pathogenesis [14][15][16][17] . However, there is increased CVD risk in patients with NAFLD even in the absence of T2DM, suggesting that NAFLD is directly causative of CVD [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, increasing evidence indicates that low-grade chronic inflammation may be the cause of several conditions and diseases associated with obesity, including type-2 diabetes, cardiovascular diseases, and fatty liver disease (Paschos and Tziomalos, 2012). In the previous chapter, it was demonstrated that hens treated with E 2 showed an increased inflammatory response as demonstrated by changes in peripheral blood (elevated leukocyte numbers and fibrinogen levels) and structural alterations of liver tissue.…”
Section: Clinical Biochemistrymentioning
confidence: 99%